Students’ Perception Towards Engaging Factors of Extreme e-Service Learning Design for Computer Network Course - Marcus, Valerie Bukas; Atan, Noor Azean; Yusof, Sanitah Mohd; Mastura, Umi (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Impact brought by COVID-19 changes the whole classroom culture from face to face to the extreme online learning and this includes a course that normally implements traditional face-to-face Service Learning. Educators are required to shift the learning into the online platform which is also known as Extreme e-Service Learning and it must be prepared in a proper way. In keeping students engaged with their learning, Extreme e-Service Learning needs to be designed based on engaging factors to encourage and support student engagement with their learning. Thus, in this study, researcher designed the Extreme e-Service Learning online platform based on the engaging factors and at the same time, investigating students’ perceptions towards this learning design. A set of questionnaires were distributed and analyzed. Semi-structured interviews with students in a smaller group were conducted to have a deeper insight. Research findings suggest that students have positive views and perceptions in regard of using Extreme e-Service Learning mainly because of the learning activities and interesting features in this online platform. This study contributed to the design of Extreme e-Service Learning based on engaging factors that help e-Service Learning instructors in planning their teaching and learning process and ensure engaging experience for the students.